Efficiency Analysis of Drum Cam-type Gear Shift Actuator - Zhong Zaimin; Duan Chengwei; Zhang Lei (Jixie chuandong)
A drum cam-type gear shift actuator based on worm and gear mechanism is introduced. The mechanical efficiency of both the worm and gear mechanism and the drum cam-type gear shift actuator are analyzed. Finally,a corresponding test rig is built for testing the mechanical efficiency of the drum cam-type gear shift actuator. The results indicate that the analysis has a certain degree of authenticity. The references for the actuator design and the optimized direction to the efficiency of the drum cam-type gear shift actuator are provided.